Inter-domain interactions in charged lipid monolayers - Caruso, Benjamin (2014)
Phase coexistence is common in model biomembranes with the presence of domains formed by lipids in a dense phase state modulating lateral diffusion of species through hydrodynamic and electrostatic interactions. In this study, interdomain interactions in monolayers of charged surfactants were analyzed and compared with neutral systems. Interactions were investigated at different interdomain distances and by varying the ionic strength (I) of the subphase. At low percentages of condensed area (%Ac), i.e., high interdomain distances, domains were approximated as point charges or dipoles, and a comparison between the simulated and experimental results was made. At high %Ac, domains were arranged in a distorted hexagonal lattice, and the energy of a domain around its equilibrium position in the lattice was modeled using a harmonic potential and the spring constant determined. On subphases of high I, charged domains interacted in a manner similar to neutral domains with domain motion being precluded at high percentages of condensed area. At low I, a higher interdomain repulsion was observed along with a lower domain motion and, therefore, a higher apparent viscosity at comparable %Ac. Interestingly, this effect was observed at conditions where the Debye-Hückel length was still 2 orders lower than the interdomain distances. © 2013 American Chemical Society.